Challenges to promoting health for amateur athletes through anti-doping policy. (4th May 2017) - Henning, April
Abstract: Anti-doping regulations are intended, at least in part, to promote the health of athletes. While most anti-doping efforts target elite and professional competitors, there have been recent moves by sport governing bodies to expand anti-doping testing to include amateur athletes. Drawing on previous critiques of anti-doping policies and illustrating cases, this article outlines five of the challenges to health promotion of applying the current detect and ban model to the amateur level of sport. I argue that the current approach is not effective and, in some ways, may undermine the goal of health promotion at the amateur level. In order to address these challenges, I propose alternative, health-centred strategies that focus on athlete empowerment and choice through critical awareness of a variety of substances, associated risks and rewards, and the role of expertise in decision-making.